VD_FINDINFO AP / 2010 / 282 vom 3. Mai 2010 - VD Tribunal cantonal (2010)
FORMATION PROFESSIONNELLE, FRAISEN GÉNÉRAL, PRÉVISIBILITÉ, SÉCURITÉ DU DROIT | 457 CPC, 23 al. 3 LFPr, 23 al. 4 LFPr, 23 al. 5 LFPr, 23 LFPr, 21 al. 2 OFPr, 21 al. 3 OFPr